Values - politics - religion: the European values study: in-depth analysis - interdisciplinary perspectives - future prospects - Polak, Regina; Rohs, Patrick (Philosophy and Politics - Critical Explorations, 2023)
Chapter 1. Introduction -- Part I: Basic Research -- Chapter 2. Values: A Contested Concept. Problem Outline and Interdisciplinary Approaches -- Chapter 3. A Critical History of the Use of ‘European Values’ -- Chapter 4. Transformations in the Religious and Moral Landscape in Europe? -- Part II: In-Depth Analysis -- Chapter 5. Political Values and Religion: A Comparison Between Western and Eastern Europe -- Chapter 6. Religion, Values and Politics: The Effect of Religiosity on Attitudes towards Immigrants and Muslims -- Chapter 7. Solidarity: A European Value? -- Chapter 8. The Invisibles: Religious and Political Values Among Different Social Classes -- Part III : Interdisciplinary Perspectives -- Chapter 9. Ethical and Theological Approaches to the Value Discourses in Europe -- Chapter 10. Values and Economy: How Companies Deal With Values -- Chapter 11. Values and Laws -- Part IV: Future Prospects -- Chapter 12. Perceptions of Social Challenges in Europe. Disentangling the Effects of Context, Social Structure, Religion, Values and Political Attitudes to Identify Potential Drivers of Societal Change -- Chapter 13. Values Education, Politics and Religion -- Chapter 14. Conclusions, Consequences, Challenges.